Formal verification of security protocols - Mok, Xin Mun (Nanyang Technological University, 2022)
Formal verification is the use of mathematical rules and logic to ensure the correctness of a system, whereby the system does not reach an undesirable state given a set of actions. Many protocols, although well documented and approved, when improperly implemented can result in the system producing an undesired outcome. This project aims to verify the correctness of modern security protocols when placed in a certain context. Specifically, the protocols used in V2V communications in a CACC system in the context of vehicle platooning.